Advertising real beer: Authenticity claims beyond truth and falsity. (October 2014) - O'Neill, Carly; Houtman, Dick; Aupers, Stef
It is a mainstay in the literature on consumer culture that the romantic, countercultural value of authenticity has become a core asset in mainstream marketing. Since there is little research on the particular ways in which commodities are endowed with auras of authenticity, this study analyses registers of authenticity in 153 beer commercials from eight countries. The content analysis distinguishes four strategies of authentication: beer is related to pre-industrial craftsmanship, naturalness, concrete locations and historical roots. Surprisingly, however, such claims are often openly exposed by the advertisers themselves as mass-produced illusions. It is concluded that the appeal of authenticity in consumer culture should not be explained by the fact that people actually believe in the 'authenticity hoax'. Quite the contrary, the acknowledgement that narratives about a more authentic world are myths provides an alibi for consumers to fully indulge in their meaning without the risk of making naive and dupable fools of themselves.